Effect of Nano and Bulk Nickel Oxide on Biomass and Antioxidant Enzymes Production of Fennel - Hilda Besharat; Ramazan Ali Khavari-Nejad; Homa Mahmoodzadeh; Khadijeh Nejad Shahrokh Abadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
The production, growth, and physiological processes of plants respond differently to the varying concentrations of nanoparticles. Due to the increasing importance and application of nanoparticles, it is essential to determine the impact on plants physiological systems. Therefore, this study investigated the effect of different bulk and nano nickel oxide concentrations on biomass production and the enzymatic system of fennel. The experiment was carried out in a completely randomized design with the applications of 5 replications and 5 concentrations (0, 20, 100, 400, and 800 ppm) in the greenhouse of the Faculty of Science, Mashhad Branch, Islamic Azad University. This study analyzed various plants traits, including shoot and dry root weight and a few antioxidant enzymes. The results showed that root and shoot dry weight were not affected by the applied treatments. Furthermore, all applied levels of treatment significantly increased the activity of fennel leaf polyphenol oxidase compared to the control. The bulk treatment at 800 ppm was exempted, where the application of bulk nickel oxide and nanoparticles decreased dehydrogenase enzyme activity. In addition, the activity of guaiacol peroxidase increased under all levels of treatments except 100 ppm nanoparticles. The highest amount of phenylalanine ammonia-lyase activity was obtained under 20 ppm treatment with a 61.98% increase compared to the control method. Furthermore, nickel oxide treatments also increased MDA. The results showed that nanomaterials' toxicity, caused oxidative stress in this plant, and the differences in MDA content of leaves explained the higher toxicity of NiO nanoparticles than bulk form. Moreover, higher activity of leaf antioxidative enzymes in bulk NiO2 treatments, especially Guaiacol Peroxidase, explained the plant's higher resistance to oxidative stress.